The Analysis of Purdue Online Writing Labs as Second Language Writing Support Tools - Meysarah, Cintya El (Yayasan Visi Intan Permata, 2018)
This study is a review of study, “the uses of and attitudes towards OWLs as second language writing support tools”, by Joshua M. Paiz in 2014. In this research review, the researcher tries to give critical views especially on methodology, the way and the instruments that the researcher used and maybe forgot. The purpose of the review, using contrastive analysis, is for consideration in conducting a further better research. Thereto, this review provides some parts specifically on steps, based on Center for Teaching Quality, in developing Purdue OWL to support L2 learning. The review agrees that using Purdue OWL for make learners easier to write is one of the valuable ways to enhance their motivation and ability especially for a second language. Unfortunately, there is still no evidence of previous research about the use of it in rural area; it makes us difficult to generalize the result of benefits in using Online Writing Labs (OWL) to other populations of practitioners.